(untitled) (Global Journal of Medical Research, 2023)
Objective To further the understanding of long-term outcomes of endometriosis patients requiring colonic segmental resection CSR or low anterior resection LAR To improve counseling of patients with bowel endometriosis Methods Retrospective chart review at a single academic institution between 2000-2018 with 3- year follow-up of patients with CSR LAR for endometriosis 21 patients aged 18-45 at single academic institution between 1 1 2000 and 12 31 2018 with ICD9 10 codes of endometriosis AND CSR LAR were included 9 met criteria for endometriosis as indication for CSR LAR were reviewed Results Pre- and post-operative symptoms were categorized into GI hematochezia dyschezia tenesmus incontinence incomplete evacuation of bowel and pre-operative colonoscopy GYN dysmenorrhea dyspareunia pelvic pain and infertility and GU dysuria frequency urgency incontinence and incomplete emptying